Strategi Peningkatan Minat Baca Siswa melalui Manajemen Waktu yang Efektif di SMA N 8 Padang - Fenia, Selvi Zola; Nadila, Nia; Parwati, Tri Ayu (LPPM Universitas Dharma Andalas, 2025)
Reading interest among high school students in Indonesia is still relatively low, which can impact academic achievement and the development of critical thinking skills. Factors such as the dominance of social media use, lack of interesting reading materials, and ineffective time management are often the main causes of low reading interest. This activity aims to provide strategies to increase the reading interest of SMA N 8 Padang students through the implementation of effective time management. These strategies include developing a regular reading schedule, applying time management techniques such as the Pomodoro method, and limiting excessive screen time. In addition, the school's role in providing attractive reading facilities, such as reading corners or digital libraries, is also an important factor. Support from teachers and parents is needed to build a sustainable reading habit. This activity was conducted at SMA N 8 Padang on January 23, 2025.